Tools and methods for optimization of databases in Oracle 10g. Part 2 – Tuning of hardware, applications and SQL queries - Barczak, Andrzej; Zacharczuk, Dariusz; Pluta, Damian (Studia Informatica. System and information technology, 2019)
Article provides information on effective optimizing of Oracle. Discussed aspects are: hardware and statistics tools on which one can build the optimal SQL code.